The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1108/jd-02-2021-0027
|View full text |Cite
|
Sign up to set email alerts
|

“Let's keep this video as real as possible”: young video bloggers constructing cognitive authority through a health-related information creation process

Abstract: PurposeThis study examines the information literacy practices of young video bloggers, focusing on the ways in which they construct their cognitive authority through a health-related information creation process.Design/methodology/approachThis study draws upon socially oriented information literacy research and nexus analysis as its methodological framework. Data, including YouTube videos, theme interviews and video diaries, were collected with three Finnish video bloggers and qualitatively analysed using nexu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 54 publications
0
2
0
1
Order By: Relevance
“…Follow-up studies indicated by the results include further consideration of the settingsbased approach in health literacy research and greater involvement of children in critical HL studies in ways that take into account children's social contexts and learning from multidisciplinary insights into participatory research, e.g., from library and information science [66]. The literature on the settings-based approach to health promotion and health literacy must continue to adapt to and absorb twenty-first-century settings into its research priorities [62], and further research building on public libraries' potential as everyday settings for health [29] and health literacy [67] should be conducted.…”
Section: Discussionmentioning
confidence: 99%
“…Follow-up studies indicated by the results include further consideration of the settingsbased approach in health literacy research and greater involvement of children in critical HL studies in ways that take into account children's social contexts and learning from multidisciplinary insights into participatory research, e.g., from library and information science [66]. The literature on the settings-based approach to health promotion and health literacy must continue to adapt to and absorb twenty-first-century settings into its research priorities [62], and further research building on public libraries' potential as everyday settings for health [29] and health literacy [67] should be conducted.…”
Section: Discussionmentioning
confidence: 99%
“…Youtuber membuat video reaksi terhadap berbagai konten dari video game, musik, dan konten daring lainnya yang bersifat "viral" . Multas & Hirvonen (2022) mendefinisikan jenis konten sebagai entitas yang digunakan untuk mengidentifikasi diri kreator serta membangun kredibilitas di mata audiens dengan menyajikan nilai tertentu. Sementara genre sebagai sub jenis yang lebih spesifik diartikan sebagai pendekatan yang begitu kuat untuk memahami isi konten serta interaksi secara "de facto" (Andersen, 2015).…”
Section: Youtuberunclassified
“…Kehollisuudella on keskeinen rooli erityisesti sosiaalisessa mediassa, jossa vuorovaikutus rakentuu usein multimodaalisen sisällön ympärille. Esimerkiksi tubettajan kehollisella tietämyksellä on keskeinen rooli uskottavan terveysaiheisen YouTube-videon luomisessa (Multas & Hirvonen, 2022). Tarvitsemme kuitenkin lisää tietoa siitä, miten kehollisuus kytkeytyy sosiaalisen median vuorovaikutukseen erityisesti vertaistuen näkökulmasta.…”
Section: Tutkimuksen Tavoite Ja Tutkimuskysymyksetunclassified